Association of weak hip abduction strength with nocturia in older women: The Nagahama study. Issue 10 (1st September 2019) - Tabara, Yasuharu; Ikezoe, Tome; Matsumoto, Takeshi; Murase, Kimihiko; Setoh, Kazuya; Funada, Satoshi; Kawaguchi, Takahisa; Nagashima, Shunsuke; Kosugi, Shinji; Hirai, Toyohiro; Nakayama, Takeo; Wakamura, Tomoko; et al.
Abstract : Aim: Nocturia is a common phenomenon in older individuals, and is associated with poor quality of life. Nocturia is a multifactorial disorder, wherein the frailty of skeletal muscles, particularly muscle weakness in the lower trunk and hip regions, might be a risk factor in women. We analyzed a dataset of the general Japanese population to clarify the hypothesis. Methods: Study participants included 1207 older women (mean age 67.4 ± 5.2 years). The frequency of nocturnal urination was assessed using a sleep diary for 1 week, and associations with lower muscle strength, skeletal muscle index, sarcopenia and physical performance (one‐leg standing time and Timed Up and Go test) were investigated. Results: The frequency of nocturnal urination more than one voiding per night was 28.1%; this frequency was inversely associated with hip abduction strength quartiles (Q1: 37.0, Q2: 30.5, Q3: 25.1 and Q4: 19.9%, P < 0.001). When a sleep diary‐based nocturnal urination frequency >1.5 times/night (corresponding to a ≥2 times/night frequency obtained by questionnaire) was considered as nocturia, logistic regression analysis adjusted for major covariates identified hip abduction strength as an independent inverse determinant of nocturia (odds ratio 0.75, 95% CI 0.52–0.90, P = 0.002). In contrast, no significant association was observed with knee extension ( P = 0.322) and hip flexion ( P = 0.603) strengths. Physical performance, skeletal muscle index and sarcopenia did not show significant associations with nocturia. Conclusions: Weak hip abduction strength might be a factor associated with nocturnal urination frequency in older women.Geriatr Gerontol Int 2019; 19: 1010–1016 .